TECHNOLOGIES OF PSYCHOLOGICAL WELL-BEIN G RESTORATION OF INTERNALLY DISPLACED PERSONS - Volodarska, Nataliia Dmitrivna (Insight: the psychological dimensions of society, 2019)
Purpose. The research purpose is to consider particularities of the body-oriented approach in restoring the well-being feeling of a person who is in a crisis situation. The urgency of the problem is outlined of the psychological wel-being formation of person in conditions of military conflict. Methods. The methods and means were identified of the body-oriented approach that were applied in the group of temporarily displaced persons. Results. The research result consists in the particularities identification of the process activation of overcoming consequences of personality psychotraumatization. Examples are given of psychotherapeutic exercises and tools in dealing with the problems of psychotraumatization of family members of internally displaced persons, as well as exercises for anxiety level and emotional stress reduction. The directions are determined of psychological support to temporarily displaced persons. Ways are identified of optimization of the process of personality adaptation, restoration of personal resource and overcoming of consequences of psychotraumatization. The methods are determined of influence on the facts that complicate, hinder or completely impede the process of psychological well-being formation. The characteristics of psychological well-being were identified in migrant groups, and these concepts were delineated in certain concepts. Conclusions. The research findings consist in the identification of directions of individual and group therapy organization. The restoration of sensibility of personality becomes a new experience, finding a new meaning of life in crisis situation, which is a key to the psychological well-being restoration. Satisfaction with life, creating stability in own thoughts and life plans, forms the well-being feeling of a human being. The first step to this consists in the determination of future life plans, goals and new life meanings. Restoration of body and thoughts interconnection, as well as feelings and experiences return back the reality feeling of personality and finding a new meaning of life in crisis situation. Feelings, emotions, experiences, as the fundamental basis of methods of the body-oriented approach, enables the personality to determine differences between its existing ideas and reality, opening to him/her the possibilities of change.